2001
DOI: 10.1002/jcp.1062
|View full text |Cite
|
Sign up to set email alerts
|

The gene PC3TIS21/BTG2, prototype member of the PC3/BTG/TOB family: Regulator in control of cell growth, differentiation, and DNA repair?

Abstract: PC3 TIS21/BTG2 is the founding member of a family of genes endowed with antiproliferative properties, namely BTG1, ANA/BTG3, PC3B, TOB, and TOB2. PC3 was originally isolated as a gene induced by nerve growth factor during neuronal differentiation of rat PC12 cells, or by TPA in NIH3T3 cells (named TIS21), and is a marker for neuronal birth in vivo. This and other ®ndings suggested its implication in the process of neurogenesis as mediator of the growth arrest before differentiation. Remarkably, its human homol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
159
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 202 publications
(170 citation statements)
references
References 93 publications
(153 reference statements)
11
159
0
Order By: Relevance
“…2). We further examine the expressions of RhoA (neurite extension [43]) and PC3 (neuronal birth [44]), resulting in no clear differences of their expression levels between the adult and embryonic NP cells. Expression of SCG10, enriched in the growth cones of the developing neurons [45], was rather decreased in the SVZ and WM cultures compared with that of E14 NP cells.…”
Section: Discussionmentioning
confidence: 99%
“…2). We further examine the expressions of RhoA (neurite extension [43]) and PC3 (neuronal birth [44]), resulting in no clear differences of their expression levels between the adult and embryonic NP cells. Expression of SCG10, enriched in the growth cones of the developing neurons [45], was rather decreased in the SVZ and WM cultures compared with that of E14 NP cells.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that Btg proteins exert cellular functions by interacting with transcriptional coactivators or corepressors, hence modulating their transcriptional activities (Matsuda et al, 2001;Tirone, 2001;Duriez et al, 2004;Lim, 2006). For example, it has been found that Btg2 impairs G1-S cell cyclephase progression by inhibiting cyclin D1 transcription (Guardavaccaro et al, 2000), that it can associate with HoxB9 (Prevot et al, 2000), and BMPregulated Smad1 and 8 (Park et al, 2004) to promote their transcriptional activity, and that it can enhance Math1 promoter activity (Canzoniere et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Btg/ Tob genes are a newly characterized family of cell cycle modulators (Guehenneux et al, 1997). Studies in different model systems suggest that they act as antiproliferative genes, they can promote cell differentiation and also regulate apoptosis and cellular senescence (Matsuda et al, 2001;Tirone, 2001;Duriez et al, 2004;Lim, 2006). Btg/Tob genes encode for a group of structurally related proteins, characterized by the presence of two novel and highly conserved domains ("antiproliferative" boxes A and B) located in the first 120 residues of the protein (Guehenneux et al, 1997;Guardavaccaro et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations